Multicultural Pedagogy Responds To The Problem Of Radicalism Entering Campus - Hendrikus Maku (Jurnal Mamangan, 2024)
This research discusses about Multicultural Pedagogy Responds to the Problem of Radicalism Entering Campus. Our social conditions today are not good. The real threat of radicalism does not only target vulnerable institutions or communities that do not have adequate immunity to thought. However, the fact that campus communities are also exposed to forbidden ideology, radicalism, is an indicator that all institutions or communities have the same potential to be exposed. This reality urges all parties, especially education practitioners and all stakeholders, to fight together against the common enemy called radicalism. Multicultural pedagogy discussed in this article is one alternative solution that can be implemented in responding to the real threat of radicalism. In addition, the roadmap to support this solution is strengthening religious moderation and a collaborative spirit from all stakeholders. United we stand, divided we fall.